Meningkatkan Motivasi Belajar Peserta Didik Kelas IV pada Mata Pelajaran Matematika dengan Menggunakan Pendekatan TaRL - Agus Lina Silvia; Ninik Srijani; Patuh Muhajir (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This research is classroom action research (PTK) which aims to determine the increase in learning motivation and learning outcomes of grade IV elementary school students in mathematics subjects through the Teaching at the Right Level (TaRL) approach. Data was collected using questionnaire and test techniques, which were carried out three times, namely at the pre-cycle stage, cycle I and cycle II. The application of the TaRL approach in mathematics learning has proven successful in increasing students' learning motivation. Based on the results of observations, the percentage of learning motivation increased from 49% in the pre-cycle to 61% in cycle I, and rose again to 78% in cycle II. Apart from that, student learning outcomes also showed a significant improvement, with the percentage of completion increasing from 56% in the pre-cycle to 70% in cycle I, and reaching 83% in cycle II, which is included in the good category.